2014
DOI: 10.7860/jcdr/2014/9436.4548
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Among Under-Five Children of Kadukuruba Tribe: Need to Reach the Unreached

Abstract: Introduction: Poor nutritional status of tribal children observed in different parts of India, calls for introspection into various factors influencing it, in order to seek remedial measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
2
16
1
Order By: Relevance
“…Mittal A et al, Manjunath R et al found no significant association between working status of mother and under nutrition. 17,18 As working mothers stay away from home for considerable time period, lack of attention towards child's feeding practices may affect nutritional status of children. Current study has revealed that mother's marital status was found to be significantly associated with stunting (P = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…Mittal A et al, Manjunath R et al found no significant association between working status of mother and under nutrition. 17,18 As working mothers stay away from home for considerable time period, lack of attention towards child's feeding practices may affect nutritional status of children. Current study has revealed that mother's marital status was found to be significantly associated with stunting (P = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though stunting among the tribal communities of Kerala is less compared to national data, it is significantly more when compared to the state prevalence (30%), denoting we are still far away from our goal of achieving reduction of stunting among tribal children. Another study, conducted in 2014 in Karnataka [4], about the nutritional status of under-five tribal children concluded that the prevalence of underweight, stunting and wasting was 60.4 %, 55.4% and 43% respectively. Similar study conducted in Maharashtra in 2012 found out that the prevalence of underweight, stunting and wasting was 64, 61 and 29%, respectively and the risk of underweight was 1.7 times higher among children of illiterate mothers and those suffering from morbidities [5].…”
Section: Discussionmentioning
confidence: 99%
“…Marasmus was more common in children between 6-12 Month (57.7)% in South east Nigeria [4]. In Uganda, Children ages between 3-24 months are at increased risk of suffering from acute Malnutrition [6]. Regional estimates of nutritional indices are usually not a reflection of the local estimate, hence this study determine nutritional status of a selected population of under-five children in Kaura Local Government located in southern part of Kaduna state, Nigeria.…”
Section: Introductionmentioning
confidence: 96%
“…The prevalence of stunting, wasting and underweight among under-five in Anambra State (South-eastern Nigeria) were 15.1%, 18.1% and 10.4% respectively [5]. An India study reported the prevalence of Underweight, Stunting and Wasting as 60.4%, 55.4% and 43% respectively [6]. One of the important risk factor to severe underweight of children in developing countries is the child feeding practices [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation